Consumer perspectives about weight management services in a community pharmacy setting in NSW, Australia. (31st May 2012) - Um, Irene S.; Armour, Carol; Krass, Ines; Gill, Timothy; Chaar, Betty B.
Abstract Background Obesity is a public health challenge faced worldwide. Community pharmacists may be well placed to manage Australia's obesity problem owing to their training, accessibility and trustworthiness. However, determining consumers' needs is vital to the development of any new services or the evaluation of existing services. Objective To explore Australian consumers' perspectives regarding weight management services in the community pharmacy setting, including their past experiences and willingness to pay for a specific pharmacy‐based service. Design An online cross‐sectional consumer survey was distributed through a marketing research company. The survey instrument comprised open‐ended and closed questions exploring consumers' experiences of and preferences for weight management services in pharmacy. It also included an attitudinal measure, the Consumer Attitude to Pharmacy Weight Management Services (CAPWMS) scale. Setting and participants A total of 403 consumers from New South Wales, Australia, completed the survey. Results The majority of respondents had previously not sought a pharmacist's advice regarding weight management. Those who had previously consulted a pharmacist were more willing to pay for and support pharmacy‐based services in the future. Most consumers considered pharmacists' motivations to provide advice related to gaining profit from selling a product and expressed concerns about the perceived conflicts of interest. Participants also perceived pharmacists as lacking expertise and time. Conclusion Although Australian consumers were willing to seek pharmacists' advice about weight management, they perceived several barriers to the provision of weight management services in community pharmacy. If barriers are addressed, community pharmacies could be a viable and accessible setting to manage obesity.